IMPLEMENTASI METODE TERM FREQUENCY INVERSED DOCUMENT FREQUENCE (TF-IDF) DAN VECTOR SPACE MODEL PADA APLIKASI PEMBERKASAN SKRIPSI BERBASIS WEB - Abdul Rokhim; Achmad ainul yaqin (STMIK YADIKA BANGIL, 2018)
Thesis is a major requirement for taking the graduation at the College of Computer Science YadikaBangil. Thesis data is stored in a database by using the application filing thesis report. This study discusses the implementation methods Term Frequency Inversed Document Frequency (TF-IDF) and the Vector Space Model on the application filing thesis report. The purpose of this study to optimize the search results in order to provide information that is more relevant to the needs of the user. With the TF-IDF method that gives weight to each - each data and vector space model calculates the value of the similarity between the keyword and each - each weight data.The result of the calculation is represented by the degree of similarity data against keyword.Keywords: Term Frequency Inversed Document Frequency (TF-IDF), Vector Space Model, Text preprocessing,laporan skripsi.